Data in legal limbo: Ownership, sovereignty, or a digital public goods regime? - Carlos María Correa (South Centre, 2020)
The legal characterization and design of a legal regime for data poses one of the most important contemporary challenges to law professionals and policy makers. How such a framework is designed matters for what kind of insertion a society will have in the digital economy, and the extent to which a country will be able to benefit from the opportunities opened by big data. The current policy space to devise legal regimes adapted to national circumstances allows countries to seek for new solutions that take into account differences in legal systems, levels of economic and technological development, and national objectives and priorities.
Keywords: 300; Big Data; Copyright; Digital Economy; Digital Public Good; Innovation; Intellectual Property; Sovereignty; Sui Generis Exclusive Rights; TRIPS